Technological and diffusion properties in the wet salting of beef assisted by ultrasound. (September 2021) - Sanches, Marcio Augusto Ribeiro; Colombo Silva, Patrícia Maria Onofre; Barretto, Tiago Luis; Darros-Barbosa, Roger; Silva-Barretto, Andrea Carla da; Telis-Romero, Javier
Abstract: The effects of the application of ultrasound and the content of NaCl in the brine on the technological and diffusion properties in the wet salting of beef were evaluated. Beef samples were immersed in brines containing different content of NaCl (100, 200 and 300 g of NaCl/L of water) and subjected to two different treatments: static brine (SB) and brine with ultrasound (US). Wet salting with ultrasound increased (P < 0.05) the NaCl content, reduced (P < 0.05) the denaturation temperature of myofibrillar proteins, reduced (P < 0.05) the water activity and did not affect (P > 0.05) the lipid oxidation of the meat when compared to samples treated in static brine (SB). The increase in the content of NaCl in the brine increased (P < 0.05) the substances reactive to thiobarbituric acid (TBARS) values of salted beef and reduced (P < 0.05) the intensity of lightness (L*), redness (a*) and yellowness (b*). None of the effects (P > 0.05) were significant for pH. Based on the results under the given operational conditions (600 W; 20 kHz), ultrasound is a technology with potential for accelerating the process of wet salting of beef, reducing the salting time and also providing technological advantages related to the properties of proteins. Highlights: Ultrasound helps reach a higher NaCl content in a shorter time on beef wet salting. Ultrasound assisted brining didn't affect lipid and color stability of salted beef. Salting with ultrasound reduced denaturation temperature and enthalpy of proteins. Limiting brine time and concentration avoid undesirable destabilization of proteins.